SPECIFICS OF DETECTION AND INVESTIGATION OF CYBERCRIME AND HIGH TECHNOLOGY OFFENCES - Zokirov Sardorjon Karimjon ugli (Scholar Express Journals, 2023)
The article examines the specifics of cybercrime and high technology offences, as well as methods and technologies for their detection and investigation. The focus is on the need for co-operation between different countries and law enforcement agencies to effectively combat these threats
Keywords: Cybercrime; high technology offences; detection; investigation